Effects of Ghrelin on intestinal cell proliferation, the expression of protein absorption and metabolism factors in juvenile grass carp (Ctenopharyngodon idella) - Yonghua Zhou (Elsevier, 2022)
Ghrelin can stimulate pituitary growth hormone (GH) release, and has a key role in the regulation of food intake and adiposity in vertebrates. At present, no relevant studies have reported the effects of Ghrelin on intestinal cell proliferation, protein absorption and metabolism. In this paper, firstly we established the intestinal epithelial cell lines of juvenile grass carp (Ctenopharyngodon idella) that can be passed stably and identified by the intestinal specific expression proteins E-cadherin and ZO-1. And we used this cell line as a model to investigate the effects of Ghrelin, Ala-Gln, Ala-Gln+Ghrelin on the proliferation of juvenile grass carp intestinal cells. We found that the use of Ghrelin, Ala-Gln and Ala-Gln+Ghrelin could promote the proliferation of intestinal cells of juvenile grass carp, but Ala-Gln+Ghrelin had the strongest promoting effect. Further, we investigated the effects of Ghrelin on the expression of cdx2, PepT1 and mTOR which are related to intestinal cell proliferation, protein absorption and metabolism of grass carp in vitro and in vivo experiments. And we studied the effects of different protein sources on the expression of Ghrelin, PepT1 and mTOR in grass carp at individual level. The results suggested that Ghrelin can promote grass carp intestinal cell proliferation, and affect the expression of genes which are related to intestinal peptide absorption and metabolism in juvenile grass carp.